The Distribuition of Strongyloides stercoralis Frequency in Araraquara, São Paulo State - Brazil - Mine, J. C. [UNESP]; Pinto, Mara Cristina [UNESP]; Martinez, I.; Allegretti, S. M.; Rosa, João Aristeu da [UNESP] (Medimond S R L, 2008)
Strongyloidiasis is a disease of emerging public health importance. A survey was conducted in Araraquara city, São Paulo state, Brazil, in order to evaluate the frequency distribution of Strongyloides stercoralis in the area. A total of 9582 single stool samples were examined by direct examination, and by the Coprotest and Rugai's methods from January 2005 to January 2007. Out of the total samples examined, 408 (4,3%) were found to be infected by S. stercoralis (143 men and 265 women). The months with the highest frequency (5,0 - 8,2%) of positive patients were February, September and December (2005); April and November (2006) and January (2007). The frequencies from the other months varied around 2,5 to 4,9%. It was concluded that strongyloidiasis is endemic in Araraquara, but in some months, which presented the highest temperatures followed by rainy periods, the frequencies are typical from hyperendemic areas.